2D/0D hierarchical heterostructures prepared via facet‐selective epitaxial growth of triangular Rh nanoplates on 2H‐Pd nanoparticles. Issue 4 (11th August 2022) - Wang, Xixi; Ge, Yiyao; Zhang, Qinghua; Lin, Ting; Chen, Bo; Li, Lujiang; Huang, Zhiqi; Yun, Qinbai; Zhou, Xichen; Shi, Zhenyu; Liu, Guanghua; Liu, Jiawei; et al.
Abstract: Phase engineering of nanomaterials opens a promising gateway to the construction of noble metal hierarchical heterostructures in a well‐defined manner. Here, by using zero‐dimensional (0D) Pd nanoparticles with hexagonal close‐packed ( hcp, 2H type) phase, denoted as 2H‐Pd, as seeds, we report a facet‐selective epitaxial growth method to prepare two‐dimensional (2D)/0D Pd@Rh hierarchical heterostructures, in which two parallel triangular Rh nanoplates selectively grow on two opposite (002)h facets of 2H‐Pd due to the confined growth of Rh along <002>h direction. Systematic characterizations demonstrate that a phase transformation from 2H phase to 2H/face‐centered cubic ( fcc ) heterophase occurs during the formation of such 2D/0D hierarchical heterostructure with the continuous growth of Rh nanoplates. The obtained 2D/0D Pd@Rh hierarchical heterostructures with a Pd/Rh atomic ratio of ∼39/61, denoted as Pd39 @Rh61, exhibit excellent performance toward electrochemical hydrogen evolution reaction (HER) in acid electrolyte. To reach the current density of 10 mA cm –2, the overpotential of only 21.3 mV is required for the 2D/0D Pd39 @Rh61, which is comparable to commercial Pt/C and also among the best Rh‐based HER catalysts reported until now. Key Points: The rational synthesis of novel 2D/0D Pd@Rh hierarchical heterostructures via the facet‐selective epitaxial growth of Rh nanoplates on Pd nanoparticles with an unconventional 2H phase is realized. Two parallel triangular Rh nanoplates selectively grow on two opposite (002)h facets of 2H‐Pd due to the confined growth of Rh along <002>h direction. 2D/0D Pd@Rh hierarchical heterostructures exhibit excellent performance toward electrochemical hydrogen evolution reaction in acid electrolyte. Abstract : 2D/0D Pd@Rh hierarchical heterostructures have been prepared via the facet‐selective epitaxial growth of two parallel triangular Rh nanoplates on two opposite (002)h facets of unconventional 2H‐Pd nanoparticles. Such hierarchical heterostructures exhibit excellent performance toward electrochemical hydrogen evolution reaction in acid electrolyte.